POES/MEPED Angular Response Functions and the Precipitating Radiation Belt Electron Flux. Issue 9 (16th September 2020) - Selesnick, R. S.; Tu, Weichao; Yando, K.; Millan, R. M.; Redmon, R. J.
Abstract: Angular response functions are derived for four electron channels and six proton channels of the SEM‐2 MEPED particle telescopes on the POES and MetOp satellites from Geant4 simulations previously used to derive the energy response. They are combined with model electron distributions in energy and pitch angle to show that the vertical 0° telescope, intended to measure precipitating electrons, instead usually measures trapped or quasi‐trapped electrons, except during times of enhanced pitch angle diffusion. A simplified dynamical model of the radiation belt electron distribution near the loss cone, as a function of longitude, energy, and pitch angle, that accounts for pitch angle diffusion, azimuthal drift, and atmospheric backscatter is fit to sample MEPED electron data at L  = 4 during times of differing diffusion rates. It is then used to compute precipitating electron flux, as function of energy and longitude, that is lower than would be estimated by assuming that the 0° telescope always measures precipitating electrons. Key Points: Angular response functions of SEM‐2 MEPED electron and proton channels are derived by Geant4 simulation Combined with a dynamical radiation belt model, they show that the 0° telescope usually detects trapped rather than precipitating electrons Model fits to sample data are used to derive precipitating electron flux at L  = 4 as a function of energy and longitude